Vitamin D Binding Protein and the Biological Activity of Vitamin D - Chun, Rene F.; Shieh, Albert; Gottlieb, Carter; Yacoubian, Vahe; Wang, Jeffrey; Hewison, Martin; Adams, John S. (Frontiers in Endocrinology, 2019)
Vitamin D has a long-established role in bone health. In the last two decades, there has been a dramatic resurgence in research interest in vitamin D due to studies that have shown its possible benefits for non-skeletal health. Underpinning the renewed interest in vitamin D was the identification of the vital role of intracrine or localized, tissue-specific, conversion of inactive pro-hormone 25-hydroxyvitamin D (25D) to active 1,25-dihydroxyvitamin D (1,25D). This intracrine mechanism is the likely driving force behind vitamin D action resulting in positive effects on human health. To fully capture the effect of this localized, tissue-specific conversion to 1,25D, adequate 25D would be required. As such, low serum concentrations of 25D would compromise intracrine generation of 1,25D within target tissues. Consistent with this is the observation that all adverse human health consequences of vitamin D deficiency are associated with a low serum 25D level and not with low 1,25D concentrations. Thus, clinical investigators have sought to define what concentration of serum 25D constitutes adequate vitamin D status. However, since 25D is transported in serum bound primarily to vitamin D binding protein (DBP) and secondarily to albumin, is the total 25D (bound plus free) or the unbound free 25D the crucial determinant of the non-classical actions of vitamin D? While DBP-bound-25D is important for renal handling of 25D and endocrine synthesis of 1,25D, how does DBP impact extra-renal synthesis of 1,25D and subsequent 1,25D actions? Are their pathophysiological contexts where total 25D and free 25D would diverge in value as a marker of vitamin D status? This review aims to introduce and discuss the concept of free 25D, the molecular biology and biochemistry of vitamin D and DBP that provides the context for free 25D, and surveys in vitro, animal, and human studies taking free 25D into consideration.